Marriage Affair In Islamic Law Anthropology Perspective - Teten Jalaludin Hayat (Mutawasith: Jurnal Hukum Islam, 2021)
The purpose of this study is to explain marriage affair or cheating in marriage as an anthropological review of Islamic law, thus, the legal wisdom should be obtained in addressing these problems. The Datas were obtained from scientific books and journals relating to the subject research theme. The research is library research, descriptive, and qualitative. The analysis technique used here was content analysis. Some of the findings research, that affair is a humanitarian epidemy that has existed throughout human history, even remains phenomenal today. Therefore, a legal wisdoms were needed in addressing these problems through the practice of religious teachings, thus the problems of cheating should suppressed and avoided, the ark of marriage can still be carried out on an ideal goal according to the anthropology of Islamic law